2019
DOI: 10.1038/s41598-019-45258-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus awareness and vaccine acceptability among men who have sex with men from mainland China

Abstract: Reductions in persistent HPV infection and related diseases occurrence have been proved among vaccinated males. However, little was known on awareness of HPV and the vaccine in males, especially in high-risk subgroups such as men who have sex with men (MSM), in China. A multicenter cross-sectional study was conducted in MSM from 10 selected cities in mainland China. HPV awareness and vaccination acceptability were investigated through interviews and questionnaires. In total, 3057 eligible participants aged 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Our electronic database search yielded 210 articles. Finally, 15 articles with a total of 8,658 participants were included ( Simatherai et al, 2009 ; Hernandez et al, 2010 ; Reiter et al, 2010 ; Wheldon et al, 2011 ; Rank et al, 2012 ; Sanchez et al, 2012 ; Gutierrez et al, 2013 ; Wang et al, 2013 ; Zou et al, 2014 ; Cummings et al, 2015 ; Giuliani et al, 2016 ; Sadlier et al, 2016 ; Zou et al, 2016 ; Nadarzynski et al, 2018 ; Li et al, 2019 ; Tian et al, 2019 ). The specific screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our electronic database search yielded 210 articles. Finally, 15 articles with a total of 8,658 participants were included ( Simatherai et al, 2009 ; Hernandez et al, 2010 ; Reiter et al, 2010 ; Wheldon et al, 2011 ; Rank et al, 2012 ; Sanchez et al, 2012 ; Gutierrez et al, 2013 ; Wang et al, 2013 ; Zou et al, 2014 ; Cummings et al, 2015 ; Giuliani et al, 2016 ; Sadlier et al, 2016 ; Zou et al, 2016 ; Nadarzynski et al, 2018 ; Li et al, 2019 ; Tian et al, 2019 ). The specific screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown high self-reported acceptance of HPV vaccination among SGM populations in some Asian countries, varying from just over 23% 115 to over 90% when they were well informed about HPV-related diseases. 116,117 Actual HPV vaccination among SGM people in Asia is understudied. Nonetheless, it is estimated that many remain unvaccinated despite the high prevalence of HPV infections.…”
Section: Hpv Vaccine Uptake In Malesmentioning
confidence: 99%
“…There are currently several HPV vaccine acceptability studies among Chinese MSM, 16–22 reporting HPV awareness ranging from 18.4% to 47.6%, acceptance of free HPV vaccination ranging from 26.2% to 97.6%, and acceptability of market price HPV vaccination ranging from 2.5% to 29.2%. In addition, although HPV and HIV infections often occur together, studies on HPV knowledge and vaccination intentions among HIV-infected MSM are scarce.…”
Section: Introductionmentioning
confidence: 99%